2017
DOI: 10.1016/j.drudis.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA and epigenetic gene regulation in renal diseases

Abstract: Kidneys have a major role in normal physiology and metabolic homeostasis. Loss or impairment of kidney function is a common occurrence in several metabolic disorders, including hypertension and diabetes. Chronic kidney disease (CKD) affect nearly 10%of the population worldwide; ranks 18th in the list of causes of death; and contributes to a significant proportion of healthcare costs. The tissue repair and regenerative potential of kidneys are limited and they decline during aging. Recent studies have demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 144 publications
0
15
0
Order By: Relevance
“…From 2013 to 2016, miRNA-mediated renal fibrosis was reviewed by some scholars from different perspectives [8,[13][14][15]. Moreover, as new research hotspots, other types of ncRNAs such as long ncRNAs and circle ncRNAs are also involved in miRNA-mediated mechanisms of renal fibrosis, such as competing endogenous RNAs (ceRNA) [16,17]. It is necessary to provide a supplementary summary of the relevant research in the recent 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…From 2013 to 2016, miRNA-mediated renal fibrosis was reviewed by some scholars from different perspectives [8,[13][14][15]. Moreover, as new research hotspots, other types of ncRNAs such as long ncRNAs and circle ncRNAs are also involved in miRNA-mediated mechanisms of renal fibrosis, such as competing endogenous RNAs (ceRNA) [16,17]. It is necessary to provide a supplementary summary of the relevant research in the recent 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-130b reportedly alleviates renal fibrosis via nail signals and collagen IV in high-glucose cultured NRK-52E cells and streptozotocin-induced DN rats [29]. A recent study showed that TGF- β may affect the expression of miR-130b, leading to renal fibrosis [30]. Upregulation of TGF- β 1 may lead to downregulation of miR-130b and aggravate renal fibrosis in DN [17].…”
Section: Discussionmentioning
confidence: 99%
“…68 ncRNAs mainly include microRNAs (miRNAs), long ncRNAs (lncRNAs), circular RNAs, small nucleolar RNAs, and transfer RNAs. 69,70 ncRNAs are regulatory RNAs, and their altered expression has been implicated in the pathogenesis of a variety of human diseases. miRNAs and lncRNAs are the two species which are more well-known and widely studied, including organ fibrosis.…”
Section: Epigenetic Modulation During Pdmentioning
confidence: 99%